Târîhu’l-arab kable’l-İslam - 880-01 Cevâd Ali, 1907-1987. (Bağdad Bağdad Bağdad Bağdad Bağdad Bağdad Bağdad)
7 cilt (1. c. 418 sayfa ; 2. c. 430 sayfa ; 3. c. 464 sayfa ; 4. c. 418 sayfa ; 5. c. 436 sayfa ; 6. c. 356 sayfa ; 7. c. 360 sayfa)